2020
DOI: 10.1021/acsbiomaterials.0c00218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of His6-Metal Assemblies as a Drug Delivery Vehicle in the Treatment of Anterior Segment Disease Using a Corneal Inflammation Model

Abstract: Keratitis is a common ophthalmological disease and also a common cause of blindness (second only to cataracts). This disease is routinely treated by topical administration of dexamethasone sodium phosphate (Dexp). However, due to the presence of anatomical and physiological barriers, frequent administration is needed, often resulting in poor patient compliance and diverse side effects. In this work, Dexp was in situ encapsulated into a His 6 -metal assembly (HmA) to generate Dexp@ HmA, which was utilized in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…As shown in Fig. 2 a, the absorbances at 240 ​nm and 280 ​nm were attributed to Dexp and BVZ [ 25 , 26 ], respectively, which were observed in Dexp&BVZ@HmA. The encapsulation of Dexp and BVZ into HmA was also supported by the FTIR spectra.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…As shown in Fig. 2 a, the absorbances at 240 ​nm and 280 ​nm were attributed to Dexp and BVZ [ 25 , 26 ], respectively, which were observed in Dexp&BVZ@HmA. The encapsulation of Dexp and BVZ into HmA was also supported by the FTIR spectra.…”
Section: Resultsmentioning
confidence: 72%
“…To address the above issues, we utilized the hexahistidine-metal assembly (HmA) formed through coordinative interaction between side imidazole group of hexahistidine and metal ions at mild conditions, which displayed encapsulating a wide spectrum of drugs with high loading efficiency [ 24 ], to coencapsulate Dexp and BVZ by a one-pot coassembly strategy. In previous studies [ 25 , 26 ], HmA exhibited a promising candidate nanocarrier of Dexp and BVZ for treating disease in anterior segment. Here, our data demonstrated that Dexp and BVZ were coloaded into Dexp&BVZ@HmA with high efficiency, while the bioactivity of BVZ was well-maintained.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the alkali burn model has low cost and easy operation [ 37 ]. Alkali burn–induced CNV is the most widely used model in the study of CNV [ [38] , [39] , [40] ].…”
Section: Methodsmentioning
confidence: 99%
“…Metal–Organic frames (MOFs) formed by coordinative interaction between metal ions and organic ligands have attracted more and more attention as drug delivery vehicles because of their facile and mild generation conditions, tunable structure, abundant assembly materials, efficient encapsulation of various materials, etc. , Encapsulating adjuvant (CpG) into the zeolitic imidazolate framework-8 (ZIF-8) had been demonstrated as subunit vaccines with potent humoral and cellular immune responses . In previous work, we reported a promising delivery system based on hexa-histidine (His 6 ) metal assemblies (HmA), which can encapsulate various drugs at mild conditions, featuring fast endocytosis and lysozyme escape. , Here, utilizing HmA, for the first time, we presented a one-pot synthesis of a subunit vaccine with a high coencapsulation efficiency and fast lysosome escape of antigen (GP100, a peptide KTWGQ­YWQV) and adjuvant (CpG ODN 1826). Our results demonstrated such generated subunit vaccines could enhance the maturation of antigen-presenting cells and stimulation of potent cellular immune response, and the strategy developed here could contribute to the future design in a subunit vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…27 In previous work, we reported a promising delivery system based on hexa-histidine (His 6 ) metal assemblies (HmA), 28 which can encapsulate various drugs at mild conditions, featuring fast endocytosis and lysozyme escape. 29,30 Here, utilizing HmA, for the first time, we presented a one-pot synthesis of a subunit vaccine with a high coencapsulation efficiency and fast lysosome escape of antigen (GP100, a peptide KTWGQYWQV) and adjuvant (CpG ODN 1826). Our results demonstrated such generated subunit vaccines could enhance the maturation of antigen-presenting cells and stimulation of potent cellular immune response, and the strategy developed here could contribute to the future design in a subunit vaccine.…”
Section: ■ Introductionmentioning
confidence: 99%